Raising Education Achievement and Breaking the Cycle of Inequality in the United Kingdom - Brook, Anne-Marie (OECD Economics Department Working Papers, 2008)
Globalisation, together with skill-biased technical change, is changing the composition of jobs in advanced economies and raising the level of skills required to do them. This has increased the importance of educating a large proportion of the population to much higher standards than in the past. The government in the United Kingdom has responded to this challenge by raising education spending and expanding the capacity of the education system in key areas such as pre-primary education and increasing participation in education beyond the age of 16. Nevertheless, performance on international tests of cognitive ability remains significantly below the standards of the best performing OECD countries and the education system seems to be particularly poor at ensuring good performance of pupils in the middle to bottom half of the education performance distribution. A renewed sense of urgency, together with some new approaches, is required to address the United Kingdom's relative underperformance in literacy and numeracy. This paper proposes a number of avenues for encouraging a higher level of educational attainment, without significant further increases in expenditure